2022
DOI: 10.2166/wpt.2022.071
|View full text |Cite
|
Sign up to set email alerts
|

Application of gated conduits for fertigation in irrigation systems

Abstract: Fertigation involves dissolving fertilizer in irrigation water, and requires uniform water distribution and fertilization. A gated conduit can be used to inject liquid fertilizers or chemicals into a pressurized irrigation system. When the conduit gate is partially opened, a vacuum draws the fluid from the suction pipe into the conduit. An experimental study was conducted to investigate the fluid-injection ratio of gated conduits, which shown to be high. The density and viscosity of the fluid were the most imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that injecting air into the flow downstream of the gate can significantly reduce the risk of cavitation damage. The air-demand ratio and the aeration efficiency in gated closed conduits have been investigated by Aydin et al (2021Aydin et al ( , 2022Aydin et al ( , 2023, Baylar and Batan (2010), Baylar et al ( , 2021Baylar et al ( , 2022, Campbell and Guyton (1953), Haindl and Sotornik (1957), Hohermuth (2017Hohermuth ( , 2019, Hohermuth et al (2020), Kalinske and Robertson (1943), Mortensen (2009), Mortensen et al (2011Mortensen et al ( , 2012, Mortensen and Kubitschek (2016), Oveson (2008), Ozkan et al (2006aOzkan et al ( , 2006bOzkan et al ( , 2010Ozkan et al ( , 2014Ozkan et al ( , 2015, Rajaratnam (1962), Safavi et al (2008), Sharma (1976), Speerli (1999), Speerli and Hager (2000), Tuna et al (2014), Unsal et al (2008Unsal et al ( , 2009Unsal et al ( , 2014, USACE (1964), Wisner (1965).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that injecting air into the flow downstream of the gate can significantly reduce the risk of cavitation damage. The air-demand ratio and the aeration efficiency in gated closed conduits have been investigated by Aydin et al (2021Aydin et al ( , 2022Aydin et al ( , 2023, Baylar and Batan (2010), Baylar et al ( , 2021Baylar et al ( , 2022, Campbell and Guyton (1953), Haindl and Sotornik (1957), Hohermuth (2017Hohermuth ( , 2019, Hohermuth et al (2020), Kalinske and Robertson (1943), Mortensen (2009), Mortensen et al (2011Mortensen et al ( , 2012, Mortensen and Kubitschek (2016), Oveson (2008), Ozkan et al (2006aOzkan et al ( , 2006bOzkan et al ( , 2010Ozkan et al ( , 2014Ozkan et al ( , 2015, Rajaratnam (1962), Safavi et al (2008), Sharma (1976), Speerli (1999), Speerli and Hager (2000), Tuna et al (2014), Unsal et al (2008Unsal et al ( , 2009Unsal et al ( , 2014, USACE (1964), Wisner (1965).…”
Section: Introductionmentioning
confidence: 99%